Acerola's pectin methylesterase: studies of heat inactivation - de Assis, S. A.; Lima, D. C.; Oliveira, OMMD (Elsevier B.V., 2000)
The effect of temperature on the activity of acerola's pectin methylesterase (PME) was studied to determine its heat-inactivation. The acerola's pectin methylesterase (PME; EC: 3.1.1.11) is very stable at 50 degrees C (10% loss of activity in 100 min) and needed 110 min for its inactivation at 98 degrees C. These values are much higher than the ones required for inactivation of the citrus PME, that has been reported as being equal to 1 min at 90 degrees C. Heat-inactivation of PME was shown to be nonlinear, suggesting the presence of fractions of PME with differing heat-stabilities. The times to inactive the enzyme at 98, 102 and 106 degrees C were 110, 10 and 2.17 min, respectively. The Z value (the rise in temperature necessary to observe a ten times faster heat-inactivation) was 4.71 degrees C. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: pectin methylesterase; inactivation enzyme; acerola